2003
DOI: 10.4049/jimmunol.171.2.717
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Phosphatidylinositol 3 Kinase-Akt Pathway in the Regulation of IL-10 and IL-12 byPorphyromonas gingivalisLipopolysaccharide

Abstract: Stimulation of the APC by Porphyromonas gingivalis LPS has been shown to result in the production of certain pro- and anti-inflammatory cytokines. However, the signaling pathways that regulate these processes are currently unknown. In the present study, the role of the phosphatidylinositol 3 kinase (PI3K)-Akt pathway in regulating P. gingivalis LPS-induced production of IL-10, IL-12 p40, and IL-12 p70 by human monocytes was investigated. P. gingivalis LPS selectively activates the PI3K-Akt pathway via Toll-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
215
4
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(248 citation statements)
references
References 83 publications
27
215
4
2
Order By: Relevance
“…It had been demonstrated that the inhibition of ERK or PI3K by selective inhibitors (PD98059 or LY294002) significantly enhanced the phenotypic and functional maturation of human MoDCs. These reports support our notion regarding the negative effects of the ERK and PI3K signaling pathways on IL-12 production, and their inhibitory effect on DC maturation (39,40). We also examined the effect of WKYMVm on the expressions of the LPS receptors TLR4 and TLR2 by using FACS.…”
Section: Discussionsupporting
confidence: 67%
“…It had been demonstrated that the inhibition of ERK or PI3K by selective inhibitors (PD98059 or LY294002) significantly enhanced the phenotypic and functional maturation of human MoDCs. These reports support our notion regarding the negative effects of the ERK and PI3K signaling pathways on IL-12 production, and their inhibitory effect on DC maturation (39,40). We also examined the effect of WKYMVm on the expressions of the LPS receptors TLR4 and TLR2 by using FACS.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, diminished CR3 outside-in signaling by the FimCDE mutants would not only result in higher IL-12 induction, but also reduced ERK1/2 activation downstream of CR3. Reduced ERK1/2 activation may in turn result in decreased production of the antiinflammatory IL-10 (Martin et al, 2003).…”
Section: In Vivo Evidence For Cr3 Exploitation By P Gingivalis and Imentioning
confidence: 99%
“…To further investigate the basis of the differential cross-regulation of the TLRs, we investigated the role of the phosphatidylinositol 3-kinase (PI3K/Akt) pathway implicated in the regulation of TLR signaling and cytokine production (Guha and Mackman, 2002;Martin et al, 2003). In mIC cl2 cells, specific inhibition of PI3K with wortmannin (Hazeki et al, 2006;Yano et al, 1993) caused an increase of NF-B luciferase activity in response to Pam 3 CSK 4 , LPS as well as flagellin (Fig.…”
Section: Contribution Of the Pi3k/akt Pathway To Tlr Cross-regulationmentioning
confidence: 99%